Answer:
y = 4
Explanation:
2x + 3y = 6
2x + y = -2
Let's set the second equation equal to y. This means that y will be alone on one side of the equal sign.
2x + y = -2
Subtract 2x from both sides.
y = -2x - 2
Now that we have y as an expression, plug it into the first equation.
2x + 3y = 6
2x + 3(-2x - 2) = 6
Distribute the 3 across the parentheses by multiplying.
2x - 6x - 6 = 6
Combine like terms.
-4x = 12
Divide both sides by -4.
x = -3
Now we have solved x.
To solve for y, plug x back into one of the equations.
y = -2x - 2
y = -2(-3) - 2
Multiply.
y = 6 - 2
Subtract.
y = 4
Check your answer by plugging both values back into the original equations.
2x + 3y = 6
2(-3) + 3(4) = 6
Multiply.
-6 + 12 = 6
Add.
6 = 6
Your answer is correct.
Hope this helps!